2009
DOI: 10.1007/s00418-009-0584-2
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic-androgenic steroid does not enhance compensatory muscle hypertrophy but significantly diminish muscle damages in the rat surgical ablation model

Abstract: Cellular responses in the compensatory hypertrophied (plantaris) muscle induced by surgical ablation of synergistic muscles (soleus and gastrocnemius) were determined during 10-week anabolic androgenic steroid (AAS) treatment. Adult Wistar male rats were divided randomly into the Control and Steroid groups, and contralateral surgery was performed. Nandrolone decanoate was administered to the Steroid group. [3H]thymidine and [14C]leucine labeling were used to determine the serial changes in cellular mitotic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…An alternative explanation for our finding is that the growth stimulus provided by SA was insufficient and was below some threshold requiring satellite cells, resulting in a false-negative, type II error. We think that this is an unlikely possibility given that SA has been shown to induce a maximal hypertrophic response that, in our hands, resulted in a twofold increase in muscle mass within two weeks (Tamaki et al, 2009a). The significant increase in Pax7 + cells, myonuclei per fiber and BrdU + positive myonuclei in the vehicle-treated group are in agreement with previous studies and support the view that satellite cells are involved in the hypertrophic response induced by SA (Akiho et al, 2010;Ishido et al, 2009).…”
Section: Research Articlesupporting
confidence: 92%
See 1 more Smart Citation
“…An alternative explanation for our finding is that the growth stimulus provided by SA was insufficient and was below some threshold requiring satellite cells, resulting in a false-negative, type II error. We think that this is an unlikely possibility given that SA has been shown to induce a maximal hypertrophic response that, in our hands, resulted in a twofold increase in muscle mass within two weeks (Tamaki et al, 2009a). The significant increase in Pax7 + cells, myonuclei per fiber and BrdU + positive myonuclei in the vehicle-treated group are in agreement with previous studies and support the view that satellite cells are involved in the hypertrophic response induced by SA (Akiho et al, 2010;Ishido et al, 2009).…”
Section: Research Articlesupporting
confidence: 92%
“…The growth response induced by SA is considered to be maximal as even the administration of an anabolic androgen failed to enhance the degree of hypertrophy (Tamaki et al, 2009a). Furthermore, it is well documented that SA induces satellite cell proliferation and the accretion of 'new', BrdU + myonuclei, presumably derived from the fusion of satellite cells (Ishido et al, 2009;Westerkamp and Gordon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…per week was much higher than the FDA-recommended analogous dosage for a human, 59 but comparable to the dosages used in other animal studies (5.6 mg/kg per day, 10 6 mg/kg per week, 30,32,57 3.75 mg/kg per week 53 ). Some studies, however, used even higher dosages (15 mg/ kg per week 6,54 ), and body builders are reported to use 10-100 times the normal therapeutic dosage of anabolic steroids.…”
Section: Discussionsupporting
confidence: 66%
“…It must be also eVective for the cells in peripheral nervous system. As supporting evidence, signiWcant increases in amino acid and thymidine uptake (Tamaki et al 2009) and the number of proliferating (positive for BrdU; 5-bromo-2Ј-deoxyuridine or PCNA; proliferating cell nuclear antigen) cells in this model have been reported (Tamaki et al , 2009. Newly myogenesis (Yamada et al 1989) and formation of branched-muscle Wbers , and increased interstitial (nonmuscle Wbers) area in the histological sections have also been reported in this model.…”
Section: Introductionmentioning
confidence: 77%
“…We recently demonstrated that this model shows near maximal responses of cellular potential in the skeletal muscle during 5-10 weeks of mechanical stretch overload, and suggested that multiple stimulation of muscle-nerve-blood vessels units (appearance of PCNA+ cells) occurs in this model (Tamaki et al 2009). Therefore, this model is considered to be suitable for analyzing physiological cellular responses in skeletal muscle totally.…”
Section: Introductionmentioning
confidence: 96%